A follow-up study on "A sensitive determination of morphine in plasma using AuNPs@UiO-66/PVA hydrogel as an advanced optical scaffold". Issue 4 (April 2023) - Karimzadeh, Zahra; Rahimpour, Elaheh; Jouyban, Abolghasem
Abstract: A double solvent-assisted approach was developed for the preparation of AuNPs@UiO-66 based polyvinyl alcohol hydrogel nanocomposite and evaluated its potential as a nanoprobe for the determination of morphine. The characterization and morphology of the synthesized platform were studied and performance comparison for morphine determination was done between the synthesized scaffold and the reported one in our previous work and discussed in detail. Due to the encapsulation of AuNPs inside UiO-66 in a double solvent-assisted approach, no energy transfer was performed with UiO-66 and finally, morphine could not bind with AuNPs. Given these values, such a hydrogel-based matrix prepared with different methodologies with the same thermal stability demonstrates dissimilar potential toward morphine determination in biological samples. Graphical abstract: Image 1